ISOLASI DAN UJI ANTAGONIS JAMUR ASAL RIZOSFER TANAMAN BAWANG MERAH (Allium ascalonicum L.) TERHADAP Alternaria porri Ellis Cif - Asri Kurniati; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to isolate and to observe the antagonicity of rhizosphere fungus from onion plant toAlternaria porri. This research has been conducted at Plant Pathology Laboratory and Plant Pest laboratory, Agriculture Faculty, University of Riau from May until July 2017. The research consisted of 6 steps as follow: 1) isolation and purification of the rhizosphere fungus from onion plant used exploration method, 2) antagonicity test of rhizosphere fungus from onion plant againstA. porri used experiment method,3) hyperparasitism test of 5 rhizosphere fungus which have a high antagonicity used observation method. Data collected from step 1 and 3 were descriptively analyzed. Data from step 2 were analyzed by using analysis of variance. The mean of each treatment were compared with Duncan’s New Multiple Range Test(DNMRT) at level 5%. Result of the research showed that there were 16isolates, 5 isolates had a high antagonicity: isolate R6, isolate R11, isolate R10, isolate R4 dan isolate R5. The isolate R6 had the best inhibition growth to A. porri (59,90%), the biggest diameter of the growth (90,00 mm) and the most rapid colony growth (25,00 mm/day). Keyword: Antagonicity,rhizosphere fungus onion